Evaluation of mix design volumetrics and cracking potential of foamed Warm Mix Asphalt (WMA) containing Reclaimed Asphalt Pavement (RAP). Issue 10 (24th August 2022) - Rahman, Mohammad Ashiqur; Zaman, Musharraf; Ali, Syed Ashik; Ghabchi, Rouzbeh; Ghos, Sagar
ABSTRACT: In this study, the mix design volumetrics and cracking potential of foamed Warm Mix Asphalt (WMA) containing various amounts of Reclaimed Asphalt Pavement (RAP) were evaluated. It was found that the increased coating ability of the foamed WMA binder counteracted the lowering of mixing and compaction temperatures for WMA. Therefore, both control HMA and foamed WMA exhibited similar mix design volumetrics up to certain lower temperatures. However, further reductions in the mixing and compaction temperatures for foamed WMA were found to exhibit improper mixing between aggregates and foamed binder. Despite foamed WMA exhibiting similar volumetric properties as HMA up to certain lower temperature, their fatigue cracking performance was found to be significantly different. The foamed WMA was found to exhibit higher cracking resistance compared to HMA in Louisiana Semi-Circular Bending (SCB) and Illinois Flexibility Index Test (I-FIT) tests. A similar trend in the cracking resistance was observed for coarser mixes in the Abrasion Loss Test (commonly known as Cantabro test). However, the Cantabro test could not screen finer mixes for their cracking resistance as it lacks a mechanistic basis. Finally, the foamed WMA technology was found to increase the cracking resistance of asphalt mixes. The higher RAP content in the foamed WMA, on the contrary was found to lower the cracking resistance of asphalt mixes due to incorporation of aged and stiffer binder from RAP.